Effect of levamisole and etimisole on the development of experimental allergic encephalomeylitis - Rysková, O; Zhitnuhin YuL; Chizhnyak, M G (Journal of hygiene, epidemiology, microbiology and immunology, 1988)
A single subcutaneous inoculation with 0.02 mg of heterologous myelin basic protein (MBP) in combination with Freund's complete adjuvant resulted in clinical and histological manifestations of experimental allergic encephalomyelitis (EAE) in 80-90% of treated guinea pigs. Daily parenteral administration of levamisole and etimisole during the latent period produced a suppressive effect on EAE development, reducing morbidity and mortality rates and preventing pathomorphological changes in the CNS. Animals receiving the drugs had decreased delayed hypersensitivity reactions to MBP in vitro. Etimisole brought about a moderate decline in the formation of circulating anti-MBP antibodies, while levamisole did not affect the strength of the humoral response, something which confirmed the primary role of cell-mediated immune reactions in the CNS demyelinization process. The reported findings may be significant in developing therapeutic strategies with respect to demyelinization diseases.
Keywords: Imidazoles; levamisol; Inflammation; imidazoly; Guinea Pigs; Spinal Cord; Levamisole; zánět; Animals; Etimizol; mícha; Encephalomyelitis, Autoimmune, Experimental; zvířata; makrofágy; tvorba protilátek; morčata; encefalomyelitida autoimunitní experimentální; etimizol; Antibody Formation; Macrophages